1994
DOI: 10.2115/fiber.50.11_526
|View full text |Cite
|
Sign up to set email alerts
|

Redox Reaction across the Membrane Incorporating Porphyrin-Linked Polymer Beads.

Abstract: Functional membranes, in which manganese meso-tetra (o-aminophenyl) porphyrin-spacer-linked polymer beads were incorporated, were prepared. The electron transfer function of the membranes was investigated by driving the conjugated redox reactions across the membranes. Consequently, it was shown that manganese porphyrin derivatives fixed to the side chains of polymer in form of beads acted as good electron carrier, while iron porphyrin, hemin, fixed to them did not. The kinetic investigation of electron tranfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…4 (b). Though this result agreed with the result reported in earlier paper (13,14) , more experiments were needed to support these assumputions. non-supported SnTCPP were indicated in Fig.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…4 (b). Though this result agreed with the result reported in earlier paper (13,14) , more experiments were needed to support these assumputions. non-supported SnTCPP were indicated in Fig.…”
Section: Introductionsupporting
confidence: 91%
“…We have previously reported an electron transfer function of polymer beads-supported manganese porphyrin, which were incorporated through the membrane (13,14). Considering this results, we have also tried to construct a photoinduced hydrogen evolution system using manganese and tin porphyrins as an electron carrier (15).…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers we reported the electron transfer function of membranes, through which manganese porphyrin-fixed hydrogel polymer beads were immobilized (17,23) . It was found that the rate of electron transfer across the membrane depends on the amount of metalloporphyrins fixed in the polymer beads, the kind of polymer beads and the presence of spacers between polymer backbone and porphyrin.…”
Section: Introductionmentioning
confidence: 99%